Sistem Perangkingan Menentukan Fakultas Terbaik Penerapan Zona Integritas Menggunakan Metode SAW - Dewi, Sri; Karo, Ichwanul Muslim Karo; Barus, Eviyona Laurenta Br (LPPM STT Terpadu Nurul Fikri, 2025)
The Integrity Zone (ZI) is defined as a designation given to government institutions that demonstrate a strong commitment from their leadership and all levels in realising a Corruption-Free Area (WBK) and/or a Clean and Serving Bureaucracy Area (WBBM). This commitment is realised through bureaucratic reform, particularly in encouraging the prevention of corrupt practices and improving the quality of public services. The purpose of this study is to build a system that will be used to see the ranking of the implementation of the faculty Integrity Zone in an effort to support corruption prevention and improve the quality of public services, so that it can assist stakeholders in decision making. Simple Additive Weighting (SAW) was applied in this study involving 7 Faculties at Medan State University, and 8 criteria were used for evaluation. The results of the study are a website-based Integrity Zone ranking system with several features that can be accessed by visitors, namely: Home, Ranking and Login, while the admin can access the Dashboard, Criteria, Alternatives, Simple Additive Weighting Calculation, and Decision Results features. The system was tested with Black Box Testing to see that the menu functions run well.